ADVERTISING AND PR AS TOOLS OF INFLUENCE IN MARKETING OF CREATIVE INDUSTRIES
The article analyzes the use of tools for influencing consumers in the marketing of creative industries. The essence of marketing of creative industries is defined. The main difference is that the marketing of creative industries works not only with rational benefit, but also with emotional value, uniqueness and cultural meaning. In the creative industries, the main force of influence is emotions, uniqueness, and cultural context. Here, the consumer buys not only a product or service, but also experience, aesthetics, identity. Thus, creative marketing is not just a set of promotion tools, but a whole strategy that combines creativity, cultural value, and business thinking. It is established that the tools of influencing consumers advertising, PR in the marketing of creative industries have not only a commercial, but also an emotional and cultural component. They work at the intersection of economics, culture and psychology. It was found that not only rational benefit is important, but also emotional value, uniqueness and cultural meaning. Creativity is not limited to "beautiful ideas." Creativity is provided by a system of tools of influence, among which advertising and PR play an important role. But marketers face a number of specific difficulties when trying to effectively use advertising and PR as tools for influencing consumers:1